2004
DOI: 10.1002/anie.200453765
|View full text |Cite
|
Sign up to set email alerts
|

Nickel‐Catalyzed Cross‐Coupling of Aryl Grignard Reagents with Aromatic Alkyl Ethers: An Efficient Synthesis of Unsymmetrical Biaryls

Abstract: Transition-metal-catalyzed cross-coupling reactions play a major role in the formation of C À C bonds. As a result, the cross-coupling of aryl halides (and pseudohalides) with organometallic reagents have become a steadfast method in organic synthesis.[1] This methodology has been used to prepare biaryl compounds, which are prevalent in both natural products and drug compounds.[2] In the more challenging cross-coupling reactions unreactive substrates, such as aryl nitriles, [3] aryl fluorides, [4] and aryl ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
102
0
3

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 284 publications
(107 citation statements)
references
References 25 publications
2
102
0
3
Order By: Relevance
“…20 The mild reaction conditions achieved allowed for the utilization of Knochel-type Grignards and, more importantly, in the presence of functional groups, a notable finding that is in sharp contrast with classical Kumada-Tamao-Corriu reactions of alkyl ethers. 9,11,12,13,18 Remarkably, it was found that cyclic vinyl ethers reacted with an exquisite stereoselectivity control, thus providing access to the rather elusive Z-homoallylic alcohols. Since other related coupling approaches invariably deliver Econfigured isomers, 21 the ability to obtain selectively Zconfigured homoallylic alcohols shows the complementarity of this method.…”
Section: Kumada-tamao-corriu Type Reactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…20 The mild reaction conditions achieved allowed for the utilization of Knochel-type Grignards and, more importantly, in the presence of functional groups, a notable finding that is in sharp contrast with classical Kumada-Tamao-Corriu reactions of alkyl ethers. 9,11,12,13,18 Remarkably, it was found that cyclic vinyl ethers reacted with an exquisite stereoselectivity control, thus providing access to the rather elusive Z-homoallylic alcohols. Since other related coupling approaches invariably deliver Econfigured isomers, 21 the ability to obtain selectively Zconfigured homoallylic alcohols shows the complementarity of this method.…”
Section: Kumada-tamao-corriu Type Reactionsmentioning
confidence: 99%
“…While the methods reported by Wenkert 9 and Dankwardt 11 established the use of aryl methyl ethers as coupling partners in Kumada-Tamao-Corriu reactions, these protocols were essentially limited to the cleavage of C(sp 2 )-O(alkyl) bonds. The Shi group described a Ni-catalyzed methodology that allowed for the coupling of activated benzyl alkyl ethers with MeMgBr via C(sp 3 )-O bond-cleavage (Scheme 11).…”
Section: Kumada-tamao-corriu Type Reactionsmentioning
confidence: 99%
“…Since the discovery of the metal-catalysed reaction by Kumada and Corriu in the early 1970s [45,46], many ligands have been reported, especially (chelating) diphosphines [47][48][49][50][51][52][53][54][55][56][57], but very few examples of metal-imidazolium salt systems have been reported. Moreover, catalytic systems involving the reaction of unactivated aryl chlorides with aryl Grignard reagents have been described only recently [58,59].…”
Section: Catalytic Studiesmentioning
confidence: 99%
“…As early as in 1979, Wenkert et al 9,10) reported the first Ni-catalyzed Kumada-Tamao type (Mg) [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] reaction, in which aryl methyl ether (ArOMe) acted as the electrophilic partner, and this is now recognized as the first example of Ni-catalyzed activation of an inert C-O bond. However, this breakthrough was overlooked for decades, until quite recently.…”
mentioning
confidence: 99%